PENGARUH PEMBERIAN PROBIOTIK PRODUK KOMERSIAL TERHADAP KADAR DO, BOD, DAN COD PADA AIR LIMBAH TAHU - Karina Izza Az Zahroh; Budi Utomo; Koosdaryani Soeryodarundio (Matriks Teknik Sipil, 2024)
The existence of quite a lot of tofu industry is actually inseparable from the risk of environmental pollution due to waste being dumped directly into waterways. Tofu wastewater needs to be treated first to meet the set quality standards before being discharged into the environment because it contains organic pollutants that can damage water. In this study, researchers used commercial probiotic products to reduce BOD and COD levels and increase DO levels in tofu wastewater. Data analysis in this study is statistical analysis by observing in the laboratory. The presentation of the data used is statistical data with a graphical method that can show the results of differences in wastewater before and after being given probiotics. The results showed that changes occurred when commercial probiotics were added to tofu wastewater. The results of the DO test showed that the ALT mixed with probiotics increased to 1.03 mg/lt at a ratio of 1:3 in 8 hours. The same results were also obtained from ALT-N which increased by 1.25 mg/lt in a ratio of 1:3 at 8 hours. In the COD and BOD tests, the levels dropped to 83.42 mg/lt and 179.47 mg/lt for ALT-N. The results showed that commercial probiotics added to tofu wastewater were able to reduce BOD and COD levels and increase DO levels.